2006
DOI: 10.1080/01919510600987685
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ozonation and Biotreatment for Forest Industry Wastewater

Abstract: This research is focused on the integrated process for the treatment of bleached Kraft pulp mill effluents. Preozonation of softwood and hardwood combined bleaching effluents at alkaline pH resulted in 50 and 44% COD abatement, respectively. Segregation of highly polluted streams of bleaching process can be recommended to reduce the cost of treatment since the COD removal yield of CEH effluents was higher than combined bleaching effluents. Moreover, biodegradability of CEH effluents in terms of BOD 5 /COD rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Ozonation is the most frequently employed AOP in combination with biological treatment processes (Bijan and Mohseni 2005;Balcioğlu et al 2006). Pre-ozonation before biological treatment can prevent process failure and improve the purification efficiency by decreasing BOD and COD load (Tuhkanen et al 1997;Thompson et al 2001).…”
Section: Ozonationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ozonation is the most frequently employed AOP in combination with biological treatment processes (Bijan and Mohseni 2005;Balcioğlu et al 2006). Pre-ozonation before biological treatment can prevent process failure and improve the purification efficiency by decreasing BOD and COD load (Tuhkanen et al 1997;Thompson et al 2001).…”
Section: Ozonationmentioning
confidence: 99%
“…Ko et al (2009) also found similar results. In addition, the reduction of COD of a bleaching wastewater from a kraft pulp and paper mill was increased by more than 25% by the addition of 5 mM Fe 2+ or Mn 2+ in comparison to its ozone treatment (Balcioglu and Moral 2008).Ozonation is the most frequently employed AOP in combination with biological treatment processes (Bijan and Mohseni 2005;Balcioğlu et al 2006). Pre-ozonation before biological treatment can prevent process failure and improve the purification efficiency by decreasing BOD and COD load (Tuhkanen et al 1997;Thompson et al 2001).…”
mentioning
confidence: 99%
“…Dielectric barrier discharge (DBD) reactors utilize electric energy to drive chemical reactions. Recent active studies involved many applications, such as the traditional ozone (O 3 ) generation [1,2] , conversion of gas phase benzene to methane [3] , partial oxidation of methane [4] , decomposition of volatile organic compounds (VOCs) [5−10] , removal of non-aqueous phase liquids from soil layers [11] , ozonation and biotreatment of forest industry wastewater [12] , treatment of skin infections, impaired microcirculation and wound healing [13] , modification of material surface [14,15] , sterilization for food and processing plants [16] , removal of nitrogen oxides (NO x ) from a gas mixture simulating exhaust gases [17] , simultaneous removal of NO x and sulphur dioxide (SO 2 ) from flue gases in a coal-combustion power plant [18] , and removal of particulate matter from diesel engine exhausts [19,20] .…”
Section: Introductionmentioning
confidence: 99%